The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.06.14.496210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cloacal virome of an ancient host lineage – the tuatara (Sphenodon punctatus) – reveals abundant and diverse diet-related viruses

Abstract: Tuatara (Sphenodon punctatus) are one of the most phylogenetically isolated species and provide a unique host system to study virus evolution. While the tuatara genome, sequenced in 2020, revealed many endogenous viral elements, we know little of the exogenous viruses that infect tuatara. We performed a metatranscriptomics study of tuatara cloaca samples from a wild population on Takapourewa (Stephens Island), Aotearoa New Zealand. From these data we identified 49 potentially novel viral species that spanned 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…It is remarkable that the genome of the virus we call MaTV because its genome was found first in maize and its ancestor teosinte, in Mexico, was also found in the cloaca of a tuatara on the tiny uninhabited island of Takpourewa (also known as Stephens Island) in New Zealand (Table 1), a wildlife refuge on which no crops are cultivated (East et al, 1995). Moreover, BCaTV and ZLaTV sequences, first described in kohlrabi and Manchurian wild rice, respectively, in China (Yang et al, 2022) were also found in the Asian long-horned tick in China (Ni et al, 2023) and in the cloaca of a tuatara in New Zealand (Waller et al, 2022). These wide distributions suggest these viruses may have wide host ranges, and perhaps rather cryptic symptomatology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is remarkable that the genome of the virus we call MaTV because its genome was found first in maize and its ancestor teosinte, in Mexico, was also found in the cloaca of a tuatara on the tiny uninhabited island of Takpourewa (also known as Stephens Island) in New Zealand (Table 1), a wildlife refuge on which no crops are cultivated (East et al, 1995). Moreover, BCaTV and ZLaTV sequences, first described in kohlrabi and Manchurian wild rice, respectively, in China (Yang et al, 2022) were also found in the Asian long-horned tick in China (Ni et al, 2023) and in the cloaca of a tuatara in New Zealand (Waller et al, 2022). These wide distributions suggest these viruses may have wide host ranges, and perhaps rather cryptic symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…to MaTV (Lappe et al, 2022). Like the MaTV genome, all eleven of these genomes were discovered in metagenomics sequencing projects using Illumina sequencing (Shi et al, 2016;Chiapello et al, 2020;Waller et al, 2022;Yang et al, 2022;Ni et al, 2023). As discussed below, all of the genomes were misannotated because ORFs were assumed to begin with an AUG codon.…”
Section: Identification Of Viruses Similar Tomentioning
confidence: 99%